Analysis of Students' Learning Activities During Virtual Laboratory Based Learning on the Excretory System - Nurlia Zahara; Hasrida Maya (Indonesian Journal of Education and Social Humanities, 2026)
Limited laboratory facilities and the lack of diverse instructional media may hinder students’ engagement in biology practicum activities, resulting in suboptimal learning activities. This study aimed to describe students’ learning activities during the implementation of a Virtual Laboratory in a urine content testing practicum on the excretory system topic at MAN 4 Aceh Besar. The study employed a pre-experimental method involving a single experimental class consisting of 35 students from class XI-2, selected through purposive sampling. Data were collected through observations of students’ learning activities using an observation sheet comprising seven indicators: visual activities, oral activities, listening activities, writing activities, mental activities, emotional activities, and drawing activities. The data were analyzed descriptively using percentage analysis. The findings revealed that the implementation of the Virtual Laboratory enhanced students’ learning activities across all observed indicators. The average percentage of students’ learning activities increased from 81% in the first meeting to 95% in the second meeting, both of which were categorized as highly active. The highest percentage in the second meeting was observed in the emotional activities indicator, reaching 100%, while all other indicators were also classified as highly active. These findings indicate that the Virtual Laboratory was effective in creating a more interactive, engaging, and student-centered learning environment, thereby increasing students’ participation throughout the learning process. Therefore, the Virtual Laboratory can serve as an effective alternative instructional medium to support biology practicum activities, particularly in teaching the excretory system.